PENINGKATAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 7 PALEMBANG MENGGUNAKAN MODEL PROJECT BASED LEARNING DENGAN PENDEKATAN CRT (CULTURALLY RESPONSIVE TEACHING) - Millenia Safitri; Rina Rina; Hetilaniar Hetilaniar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research was created to improve the quality of learning in class, low motivation in Indonesian language subjects in class VIII.9 of SMP Negeri 7 Palembang. Based on preliminary studies through observation, students have low learning motivation. Continuous learning without any innovation makes students' motivation levels low. With this research, researchers combined the Project Based Learning (PBL) learning model with the Culturally Responsive Teaching (CTR) approach. The Culturally Responsive Teaching (CTR) approach is an approach to learning that highlights the background and culture of students to be used or promoted through the material being taught, so that student involvement in learning makes the teaching and learning process more enjoyable. This research is a type of classroom action research carried out in 2 cycles. The research results show that there has been an increase in students' learning motivation obtained through motivation questionnaires. Significant results can be seen from the percentage obtained in cycle 1 which was only 73%, while in cycle 2 it was 85%. This shows that the Project Based Learning (PBL) learning model combined with the Culturally Responsive Teaching (CTR) approach is effective in increasing students' learning motivation, and the Culturally Responsive Teaching (CTR) approach makes learning more innovative.